2021
DOI: 10.1139/apnm-2020-0999
|View full text |Cite
|
Sign up to set email alerts
|

Increased cardiorespiratory stress during submaximal cycling after ketone monoester ingestion in endurance-trained adults

Abstract: There is growing interest in the effect of exogenous ketone body supplementation on exercise responses and performance. The limited studies to date have yielded equivocal data, likely due in part to differences in dosing strategy, increase in blood ketones, and participant training status. Using a randomized, double-blind, counterbalanced design, we examined the effect of ingesting a ketone monoester (KE) supplement (600 mg/kg body mass) or flavour-matched placebo in endurance-trained adults (n=10 males, n=9 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(65 citation statements)
references
References 52 publications
4
52
1
8
Order By: Relevance
“…Such an increase in PO 2 after ketone body exposure has also previously been observed in rodents after administration of 1,3-butanediol acetoacetate ketone diester during hyperbaric oxygen exposure (59). Furthermore, in line with earlier observations from our (41) and other (60) laboratories in normoxia, KE increased the hypoxic ventilatory response. This was mediated by an increase in both breathing frequency and tidal volume.…”
Section: Discussionsupporting
confidence: 91%
“…Such an increase in PO 2 after ketone body exposure has also previously been observed in rodents after administration of 1,3-butanediol acetoacetate ketone diester during hyperbaric oxygen exposure (59). Furthermore, in line with earlier observations from our (41) and other (60) laboratories in normoxia, KE increased the hypoxic ventilatory response. This was mediated by an increase in both breathing frequency and tidal volume.…”
Section: Discussionsupporting
confidence: 91%
“…1), including being fasted or fed, and being at rest or exercising, such that large variations exist in the degree of ketosis (Table 1). Ingestion of EKS, therefore, provides an alternative method to increase [R-βHB], and to a lesser extent [AcAc] [34][35][36][37][38][39], without injections or intravenous infusions [40], both of which would be impractical or illegal in most athletic contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ingestion of a KME also increased RPE (PLA, 4 ± 1; KME, 6 ± 1) following the live-burn S&R compared with PLA alone. Generally, RPE has been reported to be similar between KME and PLA conditions in previous exercise studies (9,10,31), but elevated RPE during exercise with nutritional ketosis produced by diet (46) or KME ingestion (23,30) has also been observed. For example, White et al (2007) observed a positive correlation ( r = 0.47) between elevated βHB concentrations and increased subjective states of RPE during submaximal exercise.…”
Section: Discussionmentioning
confidence: 86%
“…These findings have implications in the FF cohort, where an increase in exercise efficiency and subsequent preservation of oxygen stores can result in a FF prolong their time completing a victim S&R before exiting a burning building. However, in contrast to these data, one study recently observed an increase in exercising HR following ingestion of a KME (23). Indeed, there remains discrepancies regarding the impact that bHB might have on cardiorespiratory measures, such as HR.…”
Section: Discussionmentioning
confidence: 86%